Struvite Mineral Synthesis from Laundry Waste Water - Sutiyono; Edahwati, Luluk; Indah Nur Fauziyah; Lusy Larasati A (BIOMEJ, 2023)
Struvite is a white crystal chemically known as magnesium ammonium phosphorus hexahydrate (MgNH4PO4.6H2O). This mineral has a hardness of 1.5 to 2 Mohs. Struvite is easily soluble under acidic conditions and slightly soluble under neutral and alkaline conditions. In industry, struvite is found in the crust of pipes through which hot fluids pass. Struvite is often used as fertilizer because of its phosphate content. The formation of struvite minerals (hereinafter MAP) from laundry waste water is carried out using an aeration tank. MAP solution is made by reacting laundry waste water with Phosphoric Acid (H3PO4) and Ammonium Hydroxide (NH4OH). The MAP ratio was set at 1:1:1 with a temperature of 20 - 40 oC and an air flow rate of 0.5 - 1.5 liters per minute. The best results were at a temperature of 25oC with an air flow rate of 1 (Liter / minute) with a magnesium content of 10% and phosphorus of 42%.